Barriers to the provision of non-communicable disease care in Zimbabwe: a qualitative study of primary health care nurses - Tiny Tinashe Kamvura; Jermaine M. Dambi; Ephraim Chiriseri; Jean Turner; Ruth Verhey; Dixon Chibanda (BMC, 2022)
Abstract Background Non-communicable diseases (NCDs) contribute significantly to the global disease burden, with low-and middle-income (LMICs) countries disproportionately affected. A significant knowledge gap in NCDs exacerbates the high burden, worsened by perennial health system challenges, including human and financial resources constraints. Primary health care workers play a crucial role in offering health care to most people in LMICs, and their views on the barriers to the provision of quality care for NCDs are critical. This study explored perceived barriers to providing NCDs care in primary health care facilities in Zimbabwe. Methods In-depth, individual semi-structured interviews were conducted with general nurses in primary care facilities until data saturation was reached. We focused on diabetes, hypertension, and depression, the three most common conditions in primary care in Zimbabwe. We used thematic content analysis based on an interview guide developed following a situational analysis of NCDs care in Zimbabwe and views from patients with lived experiences. Results Saturation was reached after interviewing 10 participants from five busy urban clinics. For all three NCDs, we identified four cross-cutting barriers, a) poor access to medication and functional equipment such as blood pressure machines, urinalysis strips; b) high cost of private care; c)poor working conditions; and d) poor awareness from both patients and the community which often resulted in the use of alternative potentially harmful remedies. Participants indicated that empowering communities could be an effective and low-cost approach to positive lifestyle changes and health-seeking behaviours. Participants indicated that the Friendship bench, a task-shifting programme working with trained community grandmothers, could provide a platform to introduce NCDs care at the community level. Also, creating community awareness and initiating screening at a community level through community health workers (CHWs) could reduce the workload on the clinic nursing staff. Conclusion Our findings reflect those from other LMICs, with poor work conditions and resources shortages being salient barriers to optimal NCDs care at the facility level. Zimbabwe's primary health care system faces several challenges that call for exploring ways to alleviate worker fatigue through strengthened community-led care for NCDs. Empowering communities could improve awareness and positive lifestyle changes, thus optimising NCD care. Further, there is a need to optimise NCD care in urban Zimbabwe through a holistic and multisectoral approach to improve working conditions, basic clinical supplies and essential drugs, which are the significant challenges facing the country's health care sector. The Friendship Bench could be an ideal entry point for providing an integrated NCD care package for diabetes, hypertension and depression.